In-Situ Determination of the Charging of Nanometer and Submicron Particles at High Temperatures - Schiel, Annette; Weber, Alfred P.; Kasper, Gerhard; Schmid, Hans-Joachim (Particle & Particle Systems Characterization)
Thermal charging of submicron and nanometer particles has been studied for model aerosols of TiO2 and SiO2 as well as Al-Si (aluminosilicate) at 1 000 °C with a new quasi in-situ technique. The size dependence of the particle separation efficiency for electrostatic precipitation was determined. The charging state of the particles was obtained from evaluating the global Deutsch number for precipitation in an electric field applied to a laminar flow based on particle trajectory considerations.

In-Situ Measurement of Local Particle Flux Densities in a Complex Two-Phase Flow - Schmid, Hans-Joachim; Veith, Susanne; Umhauer, Heinz (Particle & Particle Systems Characterization)
An optical measuring technique is presented allowing the exact in-situ measurement of local particle flux densities in a confined channel flow by counting single particles penetrating an optically well defined measuring volume. This enables a precise flux determination up to the direct vicinity of planar walls. The measurement set-up and its calibration as well as the whole test facility are described in detail. This measurement technique is used to study the particle transport in electrostatic precipitators. Exemplarily, results of particle flux profiles as well as precipitation, as gained from balances of parts of the precipitator channel, are presented. Furthermore, the possibility to determine particle velocity fluctuations is demonstrated.

Trennprozesse: Abschnitt 7.5.3 - Schmid, Hans-Joachim (Handbuch der Mechanischen Verfahrenstechnik)
Summary Elektrische Staubabscheidung Wirkprinzip Mikroprozesse und Grundvorgänge Sekundäreinflüsse auf die Partikelabscheidung Wichtige Bestandteile und verschiedene Bauformen Auslegung von Abscheidern

Novel Concepts for Teaching Particle Technology - Schmid, Hans-Joachim; Peukert, Wolfgang (chemical engineering education)

On the Modelling of the Electro-Hydrodynamic Flow Field in Electrostatic Precipitators - Schmid, Hans-Joachim (Flow, Turbulence and Combustion)
Electro-hydrodynamic (EHD) flows are investigated theoretically and numerically in this paper and results are presented for the flow field in model electrostatic precipitators (EPs). The resulting flow fields are shown in various representations and explained qualitatively. Numerical calculations with different flow models (non-turbulent and RANS) were conducted to investigate the influence of the flow model on the resulting secondary flows. Furthermore, a perturbation analysis is presented, leading to a simple differential equation of the Helmholtz type. This allows a more detailed view of the important mechanisms forming the secondary flows as well as being able to obtain a very fast estimation of the resulting flow field. The calculations reveal a strong influence of a vortex formation at the beginning of the precipitation zone on the whole flow field. Furthermore, a strong effect of the boundary conditions of the electric field and the operating parameters is shown.